Determining gender differences in adolescent physical activity levels using IPAQ long form and pedometers - Vašíčková, Jana; Groffik, Dorota; Frömel, Karel; Chmelík, František; Wasowicz, Wojciech (Annals of agricultural and environmental medicine, 2013)
The need to overcome gender differences in physical activity (PA) is an essential part of health and education policy. Adolescent girls display less PA than boys. The aim of the presented research was to determine whether 4-week monitoring with pedometers can influence differences between the level of PA amongst adolescent girls and boys. Four-week interventions using pedometers, motivational brochures and the International Physical Activity Questionnaire (IPAQ), long version, and the possibility of using an Internet programme were carried out at 14 randomly selected schools. In total, 275 girls (15.8±0.9 years) and 220 boys (15.8±0.8 years) participated in the study, which was divided into intervention and control groups. The IPAQ questionnaire was applied in the pre-test as part of the ANEWS questionnaire. The IPAQ was solely used in the post-test. Significant differences in average daily steps were not observed in the intervention group for girls and boys (F=3.79; p<.05; ω(2) =.011), nor were differences in girls' average number of steps in school vs. weekend days observed (p=.82). The lowest amount of PA in boys was observed on Sunday (n=10,390±3,728 steps•day(-1)), while overall, boys had a larger amount of steps on school days than at weekends (p<.01). In contrast, girls walked more during the week following the intervention. The four-week intervention eliminated the difference in the overall PA of adolescent girls and boys, together with the difference between school and weekends among girls. The use of pedometers, motivational recording brochures and an Internet programme for maintaining PA for a longer period, supported the continuance for movement of an active and healthy lifestyle among girls significantly more than their use among boys.
Keywords: sexuální faktory; Motor Activity; mladiství; monitorování fyziologických funkcí; Data Collection; sběr dat; Sex Factors; Male; lidé; Female; mužské pohlaví; ženské pohlaví; Monitoring, Physiologic; Surveys and Questionnaires; Humans; pohybová aktivita; průzkumy a dotazníky; Adolescent